THE EFFECTIVENESS OF GAME-BASED LEARNING MODELS IN CREATING INTERACTIVE AND MEANINGFUL LEARNING - Dela ayu puspita (Teaching and General Education Studies, 2026)
Rapid technological developments and changing student characteristics require innovation in the learning process. One popular approach is Game-Based Learning (GBL), a learning model that integrates game elements to increase student engagement, motivation, and understanding of the material. This research employed a literature review method, examining various sources, including 10 books and 5 scientific journals, related to the application of Game-Based Learning in education. The study results indicate that this model can strengthen interactions between teachers and students, encourage student engagement, and help them better understand learning concepts. Furthermore, the use of games in learning activities has been shown to increase enthusiasm for learning and create a more engaging and engaging classroom atmosphere. However, implementing Game-Based Learning requires sound planning and teacher skills in managing game-based activities to ensure effective and optimal learning objectives are achieved.